THE PICTURESQUE, PORTRAITURE, AND THE MANOR HOUSE: THE SOCIAL FUNCTIONS OF ART IN MARY AUGUSTA WARD'S MARCELLA. Issue 4 (8th November 2017) - Codell, Julie
Abstract : The very first line of Mary Augusta Ward's novel Marcella ends with the word "beautiful, " repeated twice, the second time in italics. In this paper I will argue that this symbolizes the central role of aesthetics in the novel in a discourse that engages the social criticism of John Ruskin and William Morris. Some scholars have assessed Marcella (1894) as having a retrograde ending of Marcella marrying a Tory politician and landowner. Judith Wilt's critical study of Ward is entitled Behind Her Times, an indication of the general view of Ward as a political conservative, although Wilt argues that she was also progressive in many ways, and Ward has enjoyed other nuanced, sensitive re-readings and assessments (Argyle; Sutton-Ramspeck). I, too, am arguing that Ward's political and social views in this novel are complex and mixed and that examining the novel's Victorian cultural discourses can illuminate complex socio-political content that draws on late-century art world debates. The very texture of Marcella belies an unstable view of class and social problems, as the eponymous protagonist goes through several stages of thinking and trial-and-error solutions, some socialist, to problems of poverty and class disparity.